Nursing students' emotional empathy, emotional intelligence and higher education-related stress: a cross-sectional study - Jiashuang Xu; Lin Zhang; Qiqi Ji; Pengjuan Ji; Yian Chen; Miaojing Song; Leilei Guo (BMC, 2023)
Abstract Background Nursing is one of the critically important disciplines in healthcare. Due to its complexity and specificity, nursing students often face additional higher education-related stress. However, there is less research on higher education-related stress among nursing students. Therefore, the purpose of this study was to investigate the effects of emotional empathy and emotional intelligence on the dimensions of higher education-related stress among nursing students. Methods This study utilized a multi-stage sampling design and was completed within the March-June 2023 period. A total of 1126 nursing students were recruited to complete the questionnaire. The self-administered questionnaire included the basic characteristics of the subjects, an emotional empathy scale, an emotional intelligence scale, and a higher education-related stress scale. One-way ANOVA/t-tests, correlation coefficients, and hierarchical linear regression analyses were used to explore the factors affecting higher education-related stress and the relationship between emotional empathy and emotional intelligence with the dimensions of higher education-related stress. Results The mean (SD) scores of challenges and dissatisfaction dimensions of higher education-related stress among nursing students were 30.052 (7.466) and 8.270 (2.205), respectively. Emotional empathy was significantly and positively related to the challenges and dissatisfaction dimensions of higher education-related stress. Emotional intelligence was negatively correlated with the challenges dimension of higher education-related stress and positively correlated with the dissatisfaction dimension. Stratified multiple regression analyses revealed that nursing students' emotional empathy and emotional intelligence were significant predictors of the dimensions of higher education-related stress. Conclusion Overall, emotional empathy and emotional intelligence were significantly correlated with all dimensions of higher education-related stress. Consequently, in future interventions, the Chinese government and education sector can develop nursing students' ability to use emotional empathy and emotional intelligence rationally through emotional regulation strategies and emotional intelligence courses, to reduce the higher education-related stress they experience.